Methods and tools for the development of the competence of personnel in Kazakhstan. - Dzhulaeva, A.M.; Marzhanova, A.S. (Journal of Economic Research & Business Administration, 2016)
The current volatile market environment requires organizations to a qualitatively new level of implementation practices. Successful organiza-tions create new knowledge, skills, abilities, transfer them within the com-pany and quickly update the range of goods and services. Competence of the personnel has become a strategic factor for the development of the organization. The process of staff development should be ongoing. There-fore, the managers of all levels of management faced with the task of form-ing learning organizations, able to use the knowledge and experience in their work. The purpose of this article - to consider a variety of methods and tools for the development of the competence of personnel.